TI_GERICHTE 52.2016.598 vom 30. März 2017 , Estensione orario di apertura dei negozi situati all'interno di un centro commerciale - TI Tribunale d'appello (2017)
Estensione orario di apertura dei negozi situati all'interno di un centro commerciale